Risks of Small and Medium-Sized Businesses Attracting to Government and Municipal Procurement and Economic Growth - Khayrullova, A.I.; Sabitova, N.M.; Khafizova, A.R.; Nasyrova, V. I. (International Journal of Criminology and Sociology, 2022)
One of the strategic goals in the Russian Federation is to relieve social tension by increasing the number of people employed in the segment of small and medium enterprises (hereinafter - SMEs) up to 25 million people by 2024. In order to stimulate the development of this segment, the Government of the Russian Federation sets the task of expanding the access for SMEs to the procurement system. That’s why the analysis of the existing mechanism for attracting SMEs to procurement is of interest. The primary purpose of the study is to investigate the peculiarities of SME involvement in procurement within the framework of two main laws operating in the sphere of procurement activity and problems arising in the procurement’s organization and economic growth. The practice of procurement activity is accompanied by the emergence of risks that affect the procurement result. These risks are inherent both to customers and suppliers of procurement activities. In the article risks are classified by stages of procurement activity. In particular, risks of poor-quality performance of the contract arise long before the stage of its conclusion. In the conclusion, recommendations are made which can be directed to solving the issues of SMEs access to procurement.